KINERJA DAN PENDAPATAN RUMAH TANGGA ANGGOTA KELOMPOK TANI NANAS DI DESA ASTOMULYO KECAMATAN PUNGGUR KABUPATEN LAMPUNG TENGAH - Ganefo Valwigo Agus; Kordiyana K Rangga; Begem Viantimala (Lampung University, 2017)
This research aims to identify and analyze the performance of pineapple farmer group members, their household income, and the correlation between the performance and the income. This research was conducted in Astomulyo village, Punggur subdistrict, Lampung Tengah disrtrict, from Desember 2015 to March 2016. The research is a survey method using a quantitative approach. Respondents were 77 farmers, members of 11 pineapple farmer groups. The samples were determined using allocation proportional random sampling technique. The data collection was done by interviews and observation. The results showed that: 1) the performance of pineapple farmer group members is catergorized in a high classification, 2) the average household income of pineapple farmer group members is Rp66,597,177.00 per year, and 3) there is e significant correlation between the performance of members of pineapple farmer groups and the household income level. Key words: farmer group, performance, revenue